Circumscription of Tillandsia chaetophylla Mez and description of Tillandsia sessemocinoi (Bromeliaceae: Tillandsioideae) - López-Ferrari, Ana Rosa; Espejo Serna, Adolfo; Blanco Fernández de Caleya, Paloma (Instituto de Ecología, A.C., 2006)
The nomenclatural status of Tillandsia chaetophylla Mez is discussed and clarified, and a new species, Tillandsia sessemocinoi López-Ferrari, Espejo et P. Blanco, is described and illustrated. Data concerning the distribution and phenology of both taxa are provided.